(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
A set of vertices \(W’\) detour resolves a graph \(G\) if every vertex is uniquely determined by its vector of detour distances to the vertices in \(W’\). A detour metric dimension of \(G\) is the minimum cardinality of a detour resolving set of \(G\). In this paper, detour metric dimension of certain graphs are investigated by detour distance matrix.